2012
DOI: 10.5194/angeo-30-1309-2012
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen ion energization by waves in the high altitude cusp and mantle

Abstract: Abstract. We present a comparative study of low frequency electric field spectral densities and temperatures observed by the Cluster spacecraft in the high altitude cusp/mantle region. We compare the relation between the O + temperature and wave intensity at the oxygen gyrofrequency at each measurement point and find a clear correlation. The trend of the correlation agrees with the predictions by both an asymptotic mean-particle theory and a test-particle approach. The perpendicular to parallel temperature rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the latter case the divergence of the geomagnetic field lines converts the perpendicular energy into the parallel direction which increases the parallel velocity. Several acceleration mechanisms were studied such as parallel potential drops [Lundin et al, 1995;Maggiolo et al, 2006], centrifugal acceleration [Cladis, 1986;Horwitz et al, 1994;Demars et al, 1996;Nilsson et al, 2008Nilsson et al, , 2010Abudayyeh et al, 2015a] and wave-particle interaction [Chang and Coppi, 1981;Chang et al, 1986;Retterer et al, 1987Retterer et al, , 1994; Barakat and Barghouthi, 1994;Barghouthi, 1997;Barghouthi et al, 1998;Bouhram et al, 2004;Barghouthi and Atout, 2006;Barghouthi, 2008;Barghouthi et al, 2011;Slapak et al, 2011;Waara et al, 2011Waara et al, , 2012Abudayyeh et al, 2015b].…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the latter case the divergence of the geomagnetic field lines converts the perpendicular energy into the parallel direction which increases the parallel velocity. Several acceleration mechanisms were studied such as parallel potential drops [Lundin et al, 1995;Maggiolo et al, 2006], centrifugal acceleration [Cladis, 1986;Horwitz et al, 1994;Demars et al, 1996;Nilsson et al, 2008Nilsson et al, , 2010Abudayyeh et al, 2015a] and wave-particle interaction [Chang and Coppi, 1981;Chang et al, 1986;Retterer et al, 1987Retterer et al, , 1994; Barakat and Barghouthi, 1994;Barghouthi, 1997;Barghouthi et al, 1998;Bouhram et al, 2004;Barghouthi and Atout, 2006;Barghouthi, 2008;Barghouthi et al, 2011;Slapak et al, 2011;Waara et al, 2011Waara et al, , 2012Abudayyeh et al, 2015b].…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…If the heating is not sporadic, recent wave activity need not be dominating to maintain the correlation. This relation was studied by Waara et al [2012], and it was found that the correlation exists except at the highest perpendicular temperatures.…”
Section: Wave-particle Interaction (Wpi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore sporadic heating can explain a region of high temperature and relatively low wave activity. Waara et al [2012] studied this relation and found that there is indeed a correlation except at the highest perpendicular temperatures which indicates that the strongest heating is most likely sporadic. Barghouthi et al [1998] used data from the Plasma Wave Instrument on board Dynamics Explorer 1 (DE-1) to estimate the perpendicular diffusion coefficients in the polar wind for both O + and H + ions.…”
Section: Subject Classificationmentioning
confidence: 99%
“…This is a clear suggestion of further additional energization processes for outflowing O + ions at high altitudes and high latitudes in the dayside polar region. Observations indicated a significant level of electromagnetic turbulence at high altitudes above the polar cap [Gurnett et al 1984, Gurnett and Inan 1988, Waara et al 2012 which suggested an interaction known as wave-particle interaction (WPI) [Chang and Coppi 1981, Chang et al 1986, Retterer et al 1987, Crew et al 1990, Retterer et al 1994, Barghouthi 1997, Barghouthi et al 1998, Bouhram et al 2004, Waara et al 2010, Waara et al 2012]. Field aligned acceleration mechanisms such as field aligned electric fields [Lundin et al 1995, Maggiolo et al 2006] and centrifugal acceleration [Cladis 1986, Horwitz et al 1994, Demars et al 1996, Nilsson et al 2008 were also investigated to explain the energization up to kiloelectronvolt energies of O + ions above the polar cap.…”
Section: Introductionmentioning
confidence: 99%